Inhibitory effects of serotonin on transient outward potassium current in rat ventricular myocytes. - ZHAO Ming-Gao; MEI Qi-Bing; ZHANG Yan-Feng; XING Bing; LI Xiao-Qiang; CUI Yi (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of serotonin (5-hydroxy-tryptamine, 5-HT) on transient outward potassium current (I(to)) and elucidate its mechanism in rat ventricular myocytes. METHODS: I(to) was recorded using the conventional whole cell patch-clamp techniques. RESULTS: I(to) density in normal myocytes was similar to that in norepinephrine-induced hypertrophic myocytes. 5-HT depressed I(to) in a concentration-dependent manner with the half-maximal inhibitory concentration of (40+/-5) micromol/L and (38+/-7) micromol/L in normal and hypertrophic ventricular myocytes respectively. Mianserin (5-HT2 receptor antagonist), compound 48/80 (phospholipase C antagonist), and chelerythrine chloride (protein kinase C antagonist) reversed the inhibitory effects of 5-HT on I(to), while phorbol 12-myristate 13-acetate (protein kinase C agonist) enhanced the inhibitory effect of 5-HT on I(to) in normal myocytes. CONCLUSION: 5-HT markedly inhibits I(to) in rat ventricular myocytes. The putative signal pathway is that 5-HT activates phospholipase C, which causes inositol phospholipid hydrolysis. The activation of downstream signal molecule, protein kinase C, phosphorates substrate target proteins, which leads to inhibition of I(to) in ventricular myocytes.